A formal approach to rigorous development of critical systems. Issue 4 (26th January 2021) - Singh, Neeraj Kumar; Lawford, Mark; Maibaum, Thomas S. E.; Wassyng, Alan
Abstract: Safety critical systems, such as medical, automotive, and avionics systems, play an important role in our daily lives. Increasing demand for new technologies in these safety critical systems requires rapid adoption of commercial hardware and software. However, the adoption of new hardware and software increases life‐threatening vulnerabilities. To aid in the reduction of these vulnerabilities and system failures, this paper proposes a framework based on formal methods for developing safety‐critical systems from requirements analysis to code generation. This framework includes a development process for documenting system requirements using tabular expressions, automatic formal model generation from the documented requirements, verification and validation of the generated formal models using proof techniques and animations, interactive simulation for validating the required behavior of the developed models by enabling domain experts to observe the system states according to, and finally, code generation from the formal model into a desired language. A prototype toolchain is developed to automate this framework. An assessment of the proposed framework is undertaken through a case study: insulin infusion pump (IIP).